2022
DOI: 10.3389/fpls.2022.1083409
|View full text |Cite
|
Sign up to set email alerts
|

TIR1/AFB proteins: Active players in abiotic and biotic stress signaling

Abstract: The TIR1/AFB family of proteins is a group of functionally diverse auxin receptors that are only found in plants. TIR1/AFB family members are characterized by a conserved N-terminal F-box domain followed by 18 leucine-rich repeats. In the past few decades, extensive research has been conducted on the role of these proteins in regulating plant development, metabolism, and responses to abiotic and biotic stress. In this review, we focus on TIR1/AFB proteins that play crucial roles in plant responses to diverse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 120 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…However, members belonging to AFB4 and AFB5 clades had motifs 2 and 3 conserved. Similarly, Arabidopsis AFB2, AFB3, AFB4, and AFB5 showed certain conserved motifs (Du et al, 2022). This presence and absence of certain motifs indicates that TIR1/AFBs may have different functions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, members belonging to AFB4 and AFB5 clades had motifs 2 and 3 conserved. Similarly, Arabidopsis AFB2, AFB3, AFB4, and AFB5 showed certain conserved motifs (Du et al, 2022). This presence and absence of certain motifs indicates that TIR1/AFBs may have different functions.…”
Section: Discussionmentioning
confidence: 95%
“…RNA-seq expression data analysis revealed that Pyrus TIR1/ AFB genes express differently in different tissues, fruit hardening disease, and drought stress conditions. Drought stress affects the expression of multiple TIR1/AFB genes, indicating a potential role for the TIR1/AFB family in the drought tolerance pathway (Du et al, 2022). In Arabidopsis, the TIR1 showed an increased expression under drought stress (Benny et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As an auxin receptor, AtTIR1 / AFBs were induced by IAA to produce a series of responses [ 41 ], and the auxin signal transduction pathway mediated by TIR1 / AFBs was affected by auxin concentration, which was a typical auxin concentration sensing mechanism [ 2 ]. Whether the related family genes in G. hirsutum responded to the induction of IAA, the expression levels of some candidate genes were detected by RT-qPCR to apply 100 μM IAA.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect of HMs-induced stress involves the regulation of miRNAs, key factors in modulating auxin homeostasis. Recent findings show that several miRNAs are upregulated by HMs and that they target components of the auxin signalling cascade, such as TIR1, AFBs, and ARFs ( Gao et al, 2019 ; Du et al, 2022 ). This response involves the regulatory network that controls adventitious rooting, based on the interaction of miR160, 167, and ARF6, 8 , and 17 .…”
Section: Gcc Is Leading To Harsh Environmental Conditions That Induce...mentioning
confidence: 99%